(untitled) (Jurnal Agroekoteknologi dan Agribisnis, 2022)
Hydrophonic farming is widely knows as one of the inovations in modern farming, this kind of farming (hydrophonic faming) is now favored among farmers from home farming to industrial farmers. This research used qualitative descriptive research type with used data type is primary data and secondary data. This research is conducted in aim of knowing management flow from the supply chain upstream to downstream from Casafarm. As conclusion, the application of supply chain management contained